2016
DOI: 10.1073/pnas.1520489113
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor REV-ERBα mediates circadian sensitivity to mortality in murine vesicular stomatitis virus-induced encephalitis

Abstract: Certain components and functions of the immune system, most notably cytokine production and immune cell migration, are under circadian regulation. Such regulation suggests that circadian rhythms may have an effect on disease onset, progression, and resolution. In the vesicular stomatitis virus (VSV)-induced encephalitis model, the replication, caudal penetration, and survivability of intranasally applied VSV depends on both innate and adaptive immune mechanisms. In the current study, we investigated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…The second possibility is that the augmented balance between NK cells and Ly6C hi monocytes in the ZT23 group may favor a milieu conducive to efficient viral clearance and a well-contained state of inflammation. Our results are consistent with other reports where monocytes have been shown to induce excessive inflammation by different agents (Listeria and VSV) in other organs (3,10). In one model, the core clock gene Bmal1 induced Ccl2(3) while in another Rev-erbα suppressed Ccl2 (10,37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The second possibility is that the augmented balance between NK cells and Ly6C hi monocytes in the ZT23 group may favor a milieu conducive to efficient viral clearance and a well-contained state of inflammation. Our results are consistent with other reports where monocytes have been shown to induce excessive inflammation by different agents (Listeria and VSV) in other organs (3,10). In one model, the core clock gene Bmal1 induced Ccl2(3) while in another Rev-erbα suppressed Ccl2 (10,37).…”
Section: Discussionsupporting
confidence: 93%
“…Although the role of circadian regulation in systemic viral infections (8) has been described using Murid herpes virus (MHV) (9) and Vesicular Stomatis Virus (VSV) (10), its purview for respiratory viruses is limited (11). Some in vitro work (9) and results of a cluster-randomized study testing the efficacy of influenza vaccine in older adults (12) have suggested a role for circadian rhythms in influenza A infection.…”
Section: Introductionmentioning
confidence: 99%
“…16 focused on the ability of H3N1 IAV to disrupt normal clock gene expression patterns in mouse lung and proposed this event synergizes with cigarette smoke to promote chronic obstructive pulmonary disease (COPD). Finally, while this manuscript was in preparation and under review, several groups reported a role for circadian regulation in IAV, HSV, VSV and RSV infection 15, 38, 39 . Considered along with our results in SeV infection, it would appear that circadian clock function, and bmal1 in particular, is generally important for antiviral defense.…”
Section: Discussionmentioning
confidence: 99%
“…THP-1 cells treated with GSK4112 prior to LPS, decreased a range of pro-inflammatory cytokines and chemokines, including Ccl2. Interestingly, the repression of Ccl2 by REV-ERB␣ is important in the onset, progression and resolution of vesicular stomatitis virus (VSV)-induced encephalitis [125]. Mice infected at ZT0 with VSV had a significant decrease in survival rate versus those infected at ZT12.…”
Section: The Nuclear Receptors Rev-erb˛ and Rorrmentioning
confidence: 99%